Barrier spray to prevent surgical marking erasure in Mohs micrographic surgery - Sergio Schrader Serpa; Felipe Maurício Soeiro Sampaio; Felipe Bochnia Cerci (Sociedade Brasileira de Dermatologia (SBD), 2023)
The preservation of the surgical margins marking is essential during Mohs micrographic surgery. However, skin degermation during antisepsis and the use of gauze during local anesthesia often remove these markings. The use of the protective film Cavilon® 3M to fix the marking pen ink was effective in preserving the surgical map, allowing an accurate removal of the surgical specimen.